Characterization of magnetorheological fluids based on capillary magneto-rheometer - Wen, Mingfu; Du, Yueqian; Liu, Runduo; Li, Zeqin; Rao, Longshi; Xiao, Hongwei; Ouyang, Yi; Niu, Xiaodong (Frontiers in Materials, 2022)
Magnetorheological fluids (MRFs) are a class of smart magnetic controlled materials whose rheological properties can be controlled by a magnetic field. These materials have advantages of short response time, high dynamic range and low energy consumption. Due to their excellent properties, MRFs have a widely application potential in the field of impact mitigation. As the shear rate dependent viscosity of MRFs is astonishing for the shear thinning effect, thus it is crucial to study the rheological properties cross a wide range of shear rates for guiding the design and application of MRFs based adaptive impact absorbers. Commercial rotational rheometers are usually used to test the rheological properties of MRFs, but their range of measuring shear rates are limited. Commercial capillary rheometers are designed to measure the rheological behavior over a wide range of shear rates, but they’re usually lack of ability to measure with magnetic field. In order to study the rheological properties of MRFs under higher shear rate and applied magnetic field, a lab-made speed-controlled capillary magneto-rheometer is developed in the presnt work; The expressions for equivalent shear rate and apparent viscosity of MRFs under the dimensional constraint of the set-up are derived. In addition, the theoretical expression of shear rate of MRFs is modified by Rabinowitsch correction. Then, the rheological properties of three particle volume fractions（10%, 15% and 20%）of MRFs with different magnetic field strengths（6mT, 13mT, 20mT and 25mT）are tested and analyzed, and the rheological characteristic curves of MRFs with shear rate range of are obtained with the normalized characterization using Mason number. According to the experimental results, the MRFs show an obvious shear thinning phenomenon as shear rate increases, and in the Mason number based normalized characterization, the curves of different particle volume fractions are collapse to a master curve.